Cultural distance and gravity effects among migrants: A comparative analysis of the EU15 - Annie Tubadji; Peter Nijkamp (European Regional Science Association (ERSA), 2013)
This paper introduces cultural gravity as a new concept for analyzing socio-economic disparities among immigrants. It tests the existence of cultural gravity effects on the geographic concentration and human capital productivity of immigrants. Using cultural distance as a proxy for the local cultural gravity potential, the paper seeks to capture empirical evidence of the presence of significant gravity effects of culture. The paper seeks to highlight three new research issues: (i) local productivity patterns and the immigrants? contribution to them; (ii) the spatial concentration preferences of different immigrant groups; and (iii) the full culture-based development (CBD) mechanism of a joint cultural impact on the concentration and productivity of local human capital. To provide empirical evidence, we compose a cross-sectional database for the EU15, comprising inter alia the World Value Survey and Eurostat Census data, initially explored by a multivariate statistical analysis. Next, we present an extended formulation of a gravity model analyzed with appropriate regression methods, in particular explored in a logit context and through a recursive 3SLS model. Our results clearly demonstrate the existence of a cultural gravity effect among immigrants. Finally, an interesting find is that cultural gravity plays also a significant role in the context of the above-mentioned CBD growth model. The gravity model applied considers as two opposing sides the world at large and the particular locality, thus allowing the local GDP to play a role in the formation of the spatial preference among migrants. There are three specific empirical details worth notice. First, the migrants preference is expressed through a dummy variable, which is 1 when the average concentration of immigrants from a particular origin is above the average concentration of this type of immigrants around the world. Second, the recursive model is a combination of Weberian-Bourdeuian rationale for the formation of human capital in a locality, and at a second step the locally shaped human capital concoction is plugged in into a Romer-minded production function. Third, cultural distance is an innovative concept introduced to gravity modelling, quantified by the cultural capital characterizing negative cultural milieu towards the 'different' and those introducing a change. This cultural capital is measured as a vector variable, a product of factor analysis with a bunch of cultural attitudes of interest.
Keywords: Z10; O31; R12; 330; immigration; gravity; cultural distance; human capital; cultural capital; productivity